2007
DOI: 10.1590/s1807-59322007000100008
|View full text |Cite
|
Sign up to set email alerts
|

Digestive Tract Microbiota in Healthy Volunteers

Abstract: PURPOSE:The aim of this study was to standardize the methods of sample collection of mucus from the digestive tract and to determine the microbiota in healthy volunteers from Brazil, collecting samples from the mouth, esophagus, stomach, duodenum, jejunum, ileum, colon, and rectum. METHODS: Microbiota of selected healthy volunteers from the oral cavity (n=10), the esophagus (n=10), the upper digestive tract (n=20), and the lower digestive tract (n=24) were evaluated through distinct collection methods. Collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
95
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(106 citation statements)
references
References 34 publications
5
95
0
6
Order By: Relevance
“…Six species, Veillonella dispar, Veillonella parvula, Veillonella atypica, Veillonella montpellierensis, Veillonella rogosae and Veillonella denticariosi have so far been isolated from human flora whilst Veillonella ratti, Veillonella criceti, Veillonella rodentium, Veillonella caviae and Veillonella magna were only reported from non-human animal flora. Species of the genus Veillonella are usually regarded as early colonizers and highly represented members of the human microbiome, particularly in the mouth (Könönen et al, 1999) and the gut (Favier et al, 2002;Zilberstein et al, 2007), and are frequently detected during cultureindependent studies of the diversity of different microbiotae during health and disease (Paster et al, 2001;Wang et al, 2004;Aas et al, 2005;Preza et al, 2008). More frequently isolated from human clinical specimens in aerobic-anaerobic polymicrobial cultures, these bacteria were recovered in pure culture and implicated in severe opportunistic human infections (Bhatti & Frank, 2000;Marchandin et al, 2001;Boo et al, 2005;Marriott et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Six species, Veillonella dispar, Veillonella parvula, Veillonella atypica, Veillonella montpellierensis, Veillonella rogosae and Veillonella denticariosi have so far been isolated from human flora whilst Veillonella ratti, Veillonella criceti, Veillonella rodentium, Veillonella caviae and Veillonella magna were only reported from non-human animal flora. Species of the genus Veillonella are usually regarded as early colonizers and highly represented members of the human microbiome, particularly in the mouth (Könönen et al, 1999) and the gut (Favier et al, 2002;Zilberstein et al, 2007), and are frequently detected during cultureindependent studies of the diversity of different microbiotae during health and disease (Paster et al, 2001;Wang et al, 2004;Aas et al, 2005;Preza et al, 2008). More frequently isolated from human clinical specimens in aerobic-anaerobic polymicrobial cultures, these bacteria were recovered in pure culture and implicated in severe opportunistic human infections (Bhatti & Frank, 2000;Marchandin et al, 2001;Boo et al, 2005;Marriott et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of Helicobacter pylori in 1983 revealed that bacteria can in fact colonize the stomach (1). Since then, several studies on the stomach microbiota have been performed both in gastric juice and in mucosal biopsy specimens, using culture-dependent methods (2,3) as well as analysis of DNA extracted from biopsy specimens (3)(4)(5)(6)(7)(8). These studies show a previously unappreciated richness of the stomach bacterial flora but also that the communities are highly uneven and have large interindividual variation.…”
mentioning
confidence: 99%
“…These studies show a previously unappreciated richness of the stomach bacterial flora but also that the communities are highly uneven and have large interindividual variation. Commonly detected phyla include Firmicutes, Bacteriodetes, Actinobacteria, Fusobacteria, and Proteobacteria (4,5,7). These phyla are represented mainly by the genera Streptococcus, Lactobacillus, Veillonella, Clostridium, Prevotella, Porphyromonas, Rothia, Neisseria, and Haemophilus, (4,5,9,10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Согласно научным источникам [29,34,52,68], в неизмененной СОЖ наиболее распространены стрептококки, микрококки, вейлонеллы, акти-номицеты, фузобактерии, нейссерии и др.…”
Section: Introductionunclassified